2008
DOI: 10.1017/s1368980008003492
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic risk factors associated with metabolic syndrome in a Mediterranean population

Abstract: Objective: To investigate the sociodemographic risk factors associated with metabolic syndrome (MetS) in the Mediterranean population of Catalonia, Spain. Design and setting: Data from the cross-sectional, population-based [2002][2003] Health Survey of Catalonia were analysed. The survey used a structured questionnaire to collect information on demographics, lifestyle and medical history. In a sub-sample of the original survey population anthropometrics and blood pressure were measured and blood samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
49
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 41 publications
7
49
2
3
Order By: Relevance
“…In agreement with many studies [9][10][11][12][13][14][15][16][17][18], this study showed that older age, postmenopausal status, higher BMI, and smoking history were associated with elevated chances of the MetS. Compared to the youngest age group (20 -34 years), the prevalence rate in the 45 -54 years age-group were about three times higher in men and about four times higher in women.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with many studies [9][10][11][12][13][14][15][16][17][18], this study showed that older age, postmenopausal status, higher BMI, and smoking history were associated with elevated chances of the MetS. Compared to the youngest age group (20 -34 years), the prevalence rate in the 45 -54 years age-group were about three times higher in men and about four times higher in women.…”
Section: Discussionsupporting
confidence: 91%
“…In other studies, the most prevalent component was AO: 38?6 % in the USA (20) and 60?3 % in Spain (19) . The high prevalence of low HDL cholesterol observed was higher than that reported for indigenous people in Mexico (34?2 %) and for Yaquis Indians (42?4 %) (40) .…”
Section: Discussionmentioning
confidence: 62%
“…18 The mean age of our transplanted patients with MS was 47.3 years-old, which was significantly higher than in those (40.5 years-old) without the syndrome. A number of explanatory diet-and lifestyle-related risk factors are probably to be involved, affecting weight and multiple metabolic abnormalities and explaining the life course development of MS.…”
Section: Discussionmentioning
confidence: 63%